2011
DOI: 10.1002/emmm.201100168
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Runx3 expression in normal gastrointestinal epithelium calls into question its tumour suppressor function

Abstract: The Runx3 transcription factor regulates cell fate decisions during embryonic development and in adults. It was previously reported that Runx3 is strongly expressed in embryonic and adult gastrointestinal tract (GIT) epithelium (Ep) and that its loss causes gastric cancer. More than 280 publications have based their research on these findings and concluded that Runx3 is indeed a tumour suppressor (TS). In stark contrast, using various measures, we found that Runx3 expression is undetectable in GIT Ep. Employin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(87 citation statements)
references
References 42 publications
4
81
1
1
Order By: Relevance
“…Recently, studies have reported that silencing a tumor suppressor gene may result in loss of its function in tumorigenesis [16]. Inactivation mechanisms of the Runx3 gene are believed to be promoter hypermethylation and homozygous deletion [16,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, studies have reported that silencing a tumor suppressor gene may result in loss of its function in tumorigenesis [16]. Inactivation mechanisms of the Runx3 gene are believed to be promoter hypermethylation and homozygous deletion [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Inactivation mechanisms of the Runx3 gene are believed to be promoter hypermethylation and homozygous deletion [16,17]. Genetic variants of the Runx3 gene may also play an inactivation role.…”
Section: Discussionmentioning
confidence: 99%
“…1A), as was also observed by Ohno et al (25). To determine the developmental stage at which Runx3 expression is acquired, we used two Runx3 knock-in (KI) mouse strains, P1-AFP (Runx3 P1-AFP/ϩ ) and P2-EGFP (Runx3 P2-EGFP/ϩ ), harboring altered GFP (AFP) or enhanced green fluorescent protein (EGFP) inserted at the P1 or P2 ATG codon, respectively (27). Analysis of compound P1/P2-GFP mice (double heterozygote Runx3 P1-AFP/ϩ; P2-EGFP/ϩ mice) showed that ϳ60% of BM NKP (Lin (Fig.…”
Section: Expression Pattern Of Runx3 During Nkc Developmentmentioning
confidence: 99%
“…Ϫ/Ϫ , Runx3 P1-AFP/ϩ , and Runx3 P2-GFP/ϩ mice was described previously (27,28). Rag Ϫ/Ϫ ␥c Ϫ/Ϫ females were obtained from Taconic farms (stock number 004111-MM).…”
Section: Mice Generation Of Runx3mentioning
confidence: 99%
“…Despite these profound immune anomalies, in vivo studies of wound closure, contact hypersensitivity, and epidermal apoptosis were unaltered in skins of Runx3-null mice (18). Runx3 is also highly expressed in respiratory and gastrointestinal tract leukocytes, but is absent from their epithelia (13,22,23). Significantly, Runx3-null mice spontaneously develop airway and colon inflammation (19,20,22), attesting to Runx3 involvement in leukocyte homeostasis in these tissues.…”
Section: Introductionmentioning
confidence: 99%